2021
DOI: 10.3390/sports9070103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise-Induced Muscle Damage on Bowling-Specific Motor Skills in Male Adolescent Cricketers

Abstract: The current study examined the acute effects of a bout of resistance training on cricket bowling-specific motor performance. Eight sub-elite, resistance-untrained, adolescent male fast bowlers (age 15 ± 1.7 years; height 1.8 ± 0.1 m; weight 67.9 ± 7.9 kg) completed a bout of upper and lower body resistance exercises. Indirect markers of muscle damage (creatine kinase [CK] and delayed onset of muscle soreness [DOMS]), anaerobic performance (15-m sprint and vertical jump), and cricket-specific motor performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 39 publications
(62 reference statements)
1
8
0
Order By: Relevance
“…To date, the number of studies that have reported the attenuation of basic motor skills (e.g., jumping and running) during periods of EIMD has been extensive, while the investigation of EIMD on sport-specific performance measures involving speed and accuracy has been limited. In a recent study [18], a RT bout consisting of multiple upper and lower body exercises impaired ball speed and bowling accuracy during a bowling performance protocol for up to 48-h post-exercise in adolescent male, cricket fast bowlers. In addition, vertical jump, sprint performance, and run-up speed during the bowling performance protocol were also compromised.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…To date, the number of studies that have reported the attenuation of basic motor skills (e.g., jumping and running) during periods of EIMD has been extensive, while the investigation of EIMD on sport-specific performance measures involving speed and accuracy has been limited. In a recent study [18], a RT bout consisting of multiple upper and lower body exercises impaired ball speed and bowling accuracy during a bowling performance protocol for up to 48-h post-exercise in adolescent male, cricket fast bowlers. In addition, vertical jump, sprint performance, and run-up speed during the bowling performance protocol were also compromised.…”
Section: Introductionmentioning
confidence: 93%
“…These findings suggest a speed-accuracy trade-off, with athletes possibly adjusting their complex motor pattern to maintain, or enhance, performance whilst accounting for impaired muscular function. Contrarily, Doma, Leicht, Woods, Harrison, McGuckin and Connor [18] showed attenuation in both speed and accuracy during a bowling task for up to 48 h following a RT bout. The discrepancy in findings between spiking [22] and bowling performance [18] suggests that the type of sport-specific task may influence the effect of EIMD on performance outcomes.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations